Menganalisis Jaringan Sosial Penggemar Blackpink Saat Konser di Jakarta - Anggorosuryo, Ignatius; Berto, Agustinus R.; sri eko, berta (Jurnal Komunikasi Profesional, 2024)
The phenomenon of digital fandom behavior that often occurs on social media is always interesting to analyze. Social network analysis is becoming increasingly used to research this phenomenon. Social media plays an important role in providing accurate data for analysis. Twitter is the social media most used in conducting social network analysis. Based on data released (We Are Social, 2022), Twitter is the seventh favorite social media out of 16 social media platforms in the world. In Indonesia itself, according to data (dataindonesia.id, 2023), 24 million of the world's 556 million Twitter users are Indonesian. This research will analyze Black Pink as an extraordinary phenomenon with a fanatical fandom, ahead of their concert in Jakarta 10-11 March 2023. The aim of this research is to conduct a social network analysis specifically on the hashtag BORNPINKinJAKARTA, and the role of social network analysis for each Twitter user account in their relationships. This research uses Digital Fandom Theory with the Descriptive Analysis method with free Netlytics tools. This research found that the hashtag #BORNPINKInJAKARTA was the hashtag most frequently posted by Black Pink fans, which then strengthened the digital fandom theory